Analisis Konsentrasi dan Jenis Plant Growth Promoting Rhizobacteria (PGPR) Terhadap Pertumbuhan Bibit Bawang Merah (Allium ascalonicum L.) - Adrea Oktavia Rachmawati Sabira; Sulastri Isminingsih; Nur Iman Muztahidin; Kiki Roidelindho (Mediagro: Jurnal Ilmu-ilmu Pertanian, 2025)
The use of bulbs often reduces the quality of the results because the seeds often carry pathogens and reduce the productivity of shallots. One of the factors that causes the decline in the production of this plant is the lack of appropriate and effective cultivation technology. A potential solution is to improve seed quality by using organic fertilizers, especially PGPR fertilizers. This study aims to determine the concentration and type of PGPR that affect the growth of shallot seeds. The research method used was a randomized block design consisting of two factors, namely; PGPR concentration consisting of three levels, namely 10 ml / l (K1), 20 ml / l (K2), and 30 ml / l (K3). The second factor is the type of PGPR consisting of 3 levels, including: mimosa pudica roots (P1), bamboo roots (P2), and elephant grass roots (P3). The results showed that the PGPR concentration of 20 ml / l (K2) gave the best effect on the parameters of plant height and leaf length. Among the types of PGPR, bamboo roots (P2) gave the best results on the parameters of plant height, number of leaves and leaf length. There is also an interaction between the concentration and type of PGPR on plant height and leaf length parameters.